2018
DOI: 10.1186/s12967-018-1577-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an early diagnostic biomarker of lung adenocarcinoma based on co-expression similarity and construction of a diagnostic model

Abstract: BackgroundThe purpose of this study was to achieve early and accurate diagnosis of lung cancer and long-term monitoring of the therapeutic response.MethodsWe downloaded GSE20189 from GEO database as analysis data. We also downloaded human lung adenocarcinoma RNA-seq transcriptome expression data from the TCGA database as validation data. Finally, the expression of all of the genes underwent z test normalization. We used ANOVA to identify differentially expressed genes specific to each stage, as well as the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Specifically, in [69] a SVM was used to classify 445 adenocarcinoma (AC) and 19 normal (N) samples from RNA-seq data using 44 gene features. Also in [70] a SVM was used. In their case, 73 adenocarcinoma (AC) and 80 normal (N) samples from RNA-seq data were classified using 12 gene features.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, in [69] a SVM was used to classify 445 adenocarcinoma (AC) and 19 normal (N) samples from RNA-seq data using 44 gene features. Also in [70] a SVM was used. In their case, 73 adenocarcinoma (AC) and 80 normal (N) samples from RNA-seq data were classified using 12 gene features.…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies only used DEGs or the first 25% variation genes to construct a weighted gene co-expression network, which may result in a loss of genetic diversity. Moreover, some studies only used the feature selection method to select biomarkers ( 17 , 43 , 48 ). Although this method can reduce the dimensionality of data, these genes that play important roles in the cancer process may be lost.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, WGCNA was widely applied to screen hub genes in various cancers (9). This approach can identify critical cancer driver genes that may be a significant therapeutic target or diagnostic marker (43). In recent years, several biomarkers have been identified in the field of cancer research using WGCNA (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SPP1 has been identified as a prognostic biomarker in four LUAD datasets in the GEO database, which was also validated by the TCGA database [ 13 ]. Fan et al suggested 12 significant biomarkers that could distinguish lung cancer patients with different risks from the GEO database [ 14 ]. Gan et al identified the aberrantly expressed miR-375 gene involved in LUAD through the comparison of miRNA expression profiles in cancerous tissues based on the analysis and validation from TCGA and GEO datasets and published studies[ 15 ].…”
Section: Discussionmentioning
confidence: 99%